Dietary fungi in cancer immunotherapy: From the perspective of gut microbiota - Wei, Yibing; Song, Dingka; Wang, Ran; Li, Tingting; Wang, Hui; Li, Xiaoguang (Frontiers in Oncology, 2023)
Immunotherapies are recently emerged as a new strategy in treating various kinds of cancers which are insensitive to standard therapies, while the clinical application of immunotherapy is largely compromised by the low efficiency and serious side effects. Gut microbiota has been shown critical for the development of different cancer types, and the potential of gut microbiota manipulation through direct implantation or antibiotic-based depletion in regulating the overall efficacy of cancer immunotherapies has also been evaluated. However, the role of dietary supplementations, especially fungal products, in gut microbiota regulation and the enhancement of cancer immunotherapy remains elusive. In the present review, we comprehensively illustrated the limitations of current cancer immunotherapies, the biological functions as well as underlying mechanisms of gut microbiota manipulation in regulating cancer immunotherapies, and the benefits of dietary fungal supplementation in promoting cancer immunotherapies through gut microbiota modulation.